[PP.02.18] AZILSARTAN MEDOXOMIL DECREASES 24-H CENTRAL BP AND ARTERIAL STIFFNESS IN PATIENTS WITH ARTERIAL HYPERTENSION AND TYPE 2 DIABETES MELLITUS. (September 2017) - Starostina, E.; Troitskaya, E.; Kulakov, V.; Villevalde, S.; Kobalava, Z.
Abstract : Objective: Achievement of target blood pressure (BP) is the main strategy of the prevention of cardio-vascular (CV) events in patients with type 2 diabetes mellitus (T2DM). Central aortic systolic blood pressure (SBP) is a better predictor of CVD and a better guide for anti-hypertensive treatment compared to brachial SBP. Azilsartan medoxomil (AZM) has shown greater antihypertensive efficacy compared to other angiotensin receptor blockers (ARB). The aim of the study was to evaluate changes in office and 24-h central BP (CBP) and parameters of arterial stiffness in patients with AH and T2DM receiving ineffective free dual combination after replacement of renin-angiotensin-aldosteroneinhibitor (iRAAS) by AZM. Design and method: 30 patients with AH and T2DM with uncontrolled blood pressure >140/85 mmHg on dual AHT were included (53% females, mean age 60.4 ± 7.6 years (M ± SD), 40% smokers). 63% received ACE inhibitors, 37% - other ARB. The other drug was thiazide diuretic in 57%, CCB in 30% and BB in 13%. RAAS inhibitor was replaced by 40 mg of AZM with up-titration to 80 mg after 6 weeks in the case of uncontrolled AH. Study duration was 12 weeks. BP was measured with a validated oscillometric device (OMRON 705CP-II). Arterial stiffness was measured by applanation tonometry (SphygmoCor, AtCor). 24-h peripheral and central BP monitoring was performed (BPLab Vasotens, "Petr Telegin"). P < 0.05 was significant. Results: After 12 weeks target BP was achieved in 25 (83%) patients. Up titration of AZM was performed in 11 (37%) patients. Office CBP significantly decreased from 144 ± 11/84 ± 4 mmHg to 115 ± 9/67 ± 5 mmHg respectively, p < 0.05. Baseline and achieved 24-h CBP levels were as follows: 136 ± 15/82 ± 9 and 118 ± 11/69 ± 5 mmHg for daytime; 129 ± 21/74 ± 11 and 110 ± 8/64 ± 5 mmHg for nighttime; 134 ± 17/80 ± 11 and 114 ± 9/66 ± 5 mmHg for 24-h, respectively p < 0.05 for trend. There were also significant changes in the parameters of arterial stiffness: pulse wave velocity decreased from 10.2 ± 2.3 to 9.5 ± 2.2 m/s; AIx@75 from 25 ± 9 to 13 ± 7%, p < 0.05. No changes in PP amplification were observed. Conclusions: Replacement of RAAS inhibitor by AZM results in significant decrease of office and 24-h central BP and improvement of parameters of AS in patients with T2DM and uncontrolled AH.